Entrepreneurship Education and Perceived Behavioral Control Toward Social Entrepreneurship Intention University Student in Indonesia - Faadhilah, Kamilia Hanna; Kurjono (Universitas Muhammadiyah Surakarta, 2023)
The research aims to examine how entrepreneurship education and perceived behavioral control affect social entrepreneurial intentions. It also investigates whether entrepreneurial tendencies can moderate the relationship between the two variables in Accounting Education students throughout Indonesia. The theory used to determine the intention of social entrepreneurship is the Theory of Planned Behavior (TPB). According to TPB, the intention to perform a behavior can be examined from attitudes, subjective norms, and perceived behavioral control. This research is expected to contribute to increasing entrepreneurial intention, especially in the field of social entrepreneurship. This research used a quantitative methodological approach with a survey research method in the form of distributing questionnaires to a sample of 372 respondents. The results indicated that both entrepreneurship education and perceived behavioral control significantly influence social entrepreneurship intention. However, it was observed that entrepreneurial tendency does not moderate the relationship between entrepreneurship education and social entrepreneurship intention. It is recommended to improve the quality of entrepreneurship education programs by integrating a curriculum that is relevant to students need and developing the skills needed for entrepreneurship. This will encourage the development of an entrepreneurial mindset and creativity through entrepreneurship education programs.